Cash management (advanced systems) - Duruorjiaku, G. O. (Lagos : G. O. Duruorjiaku & Co., 2001)
The book keeps one up-to-date with new technologies in networks on computer systems to the latest data communication equipment for cash work and gives ideas in management and control of cash.
oif 10/02/15
Loan
Keywords: Cash management; Banks and banking